Black liver in a patient with Wilson's disease. Issue 11 (6th November 2022) - Jiang, Wei; Zeng, Qingmin; Liu, Chang‐Hai; Wu, Dongbo; Tang, Hong
Abstract: Wilson's disease is an autosomal recessive inherited disease with congenital copper metabolism disorder, characterized by decreased ceruloplasmin and increased urine copper, which can involve multiple organs. This case was complicated by iron overload, which is of great value in differentiating hereditary hemochromatism. Abstract : When Wilson's disease presents increased serum iron and liver iron deposition, liver MRI shows black liver image, and liver pathology shows iron deposition in zone 2–3. At this time, it is necessary to identify with hereditary hemochromatism.